Implementasi Pemungutan Pajak Kendaraan Bermotor Dan Bermobil Dalam Meningkatkan Sistem Layanan Samsat Drive Thru Dan Pengaruhnya Terhadap Kepatuhan Wajib Pajak Pada Kantor Samsat di Kota Makassar - Hasan, Hamida; Rifani, Riza Amalia (Pusat Penerbitan dan Publikasi Ilmiah FEB-UMI, 2022)
The purpose of this study is to analyze the collection of motorized vehicle taxes and cars in improving the drive-thru Samsat service system at the Samsat Office in Makassar City the results of the analysis, it shows that the collection of motorized vehicle taxes has a positive and significant effect in improving the drive-thru Samsat service system. Based on the results of the analysis showed that the collection of motor vehicle tax has a positive and significant effect in increasing taxpayer compliance. Based on the results of the analysis, it shows that the drive-thru samsat service system has a positive and significant effect on increasing taxpayer compliance. Based on the results of the analysis, it is shown that the collection of motorized and motorized vehicle taxes through the implementation of the Samsat drive thru service system can increase taxpayer compliance at the Samsat Office in Makassar City.